9 | = | x |

| |

x | 1 |

Cross multiply:
9 * 1 = x * x
Simplifying
9 * 1 = x * x
Multiply 9 * 1
9 = x * x
Multiply x * x
9 = x

^{2}
Solving
9 = x

^{2}
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x

^{2}' to each side of the equation.
9 + -1x

^{2} = x

^{2} + -1x

^{2}
Combine like terms: x

^{2} + -1x

^{2} = 0
9 + -1x

^{2} = 0
Add '-9' to each side of the equation.
9 + -9 + -1x

^{2} = 0 + -9
Combine like terms: 9 + -9 = 0
0 + -1x

^{2} = 0 + -9
-1x

^{2} = 0 + -9
Combine like terms: 0 + -9 = -9
-1x

^{2} = -9
Divide each side by '-1'.
x

^{2} = 9
Simplifying
x

^{2} = 9
Take the square root of each side:
x = {-3, 3}